Thioredoxin-1 Activation by Pterostilbene Protects Against Doxorubicin-Induced Hepatotoxicity via Inhibiting the NLRP3 Inflammasome - Tan, Shiqing; Bai, Jie; Xu, Mingxi; Zhang, Longying; Wang, Ying (Frontiers in Pharmacology, 2022)
Background: Doxorubicin (DOX) has been widely used in cancer treatment. However, DOX can cause a range of significant side effects, of which hepatotoxicity is a common one, and therefore limits its clinical use. Pterostilbene (PTS) has been shown to exhibit anti-oxidant and anti-inflammatory effects in the treatment of liver diseases but whether PTS could protect against hepatotoxicity in DOX-treated mice is unknown. Methods: In our study, we use C57/BL6J mice and the HepG2 cell line. We divided the mice in 4 groups: the control, the PTS treatment, the DOX treatment, and the DOX + PTS treatment group. Liver histopathology was judged by performing hematoxylin–eosin and Masson staining. Immunohistochemistry was used to perform the expression of NLRP3. The levels of serum alanine transaminase (ALT) and aspartate transaminase (AST) were evaluated. Levels of malondialdehyde (MDA), superoxide dismutase (SOD), glutathione (GSH), and DCFH-DA staining were used to evaluate the oxidative injury. Western blot and real-time PCR were applied to evaluate the expressions of proteins and mRNA. MTT was used to evaluate DOX-induced cell injury and the protective effects of PTS. Recombinant Trx-1 was used to analyze the mechanism of PTS. A TUNEL assay was used to detect apoptosis in DOX-induced HepG2 cells and the protective effects of PTS. Results: PTS ameliorated DOX-induced liver pathological changes and the levels of AST and ALT. PTS also decreased the level of MDA, increased the level of SOD, GSH, and the expression of Trx-1 in DOX-treated mice. PTS decreased the levels of NLRP3 and IL-1β mRNA and the expressions of their proteins in DOX-treated mice. In addition, PTS also decreased the expression of Cleaved Caspase-3 and BAX and increased the expression of BCL-2. In vitro, after treatment with recombinant Trx-1, ROS and NLRP3 inflammasome were both decreased. Treatment with PTS could rescue the downregulation of Trx-1, decreased the ROS level and the NLRP3 inflammasome, and protected HepG2 cells against DOX-induced apoptosis. Conclusion: The results show that PTS exhibits protective effects against DOX-induced liver injuries via suppression of oxidative stress, fibrosis, NLRP3 inflammasome stimulation, and cell apoptosis which might lead to a new approach of preventing DOX-induced hepatotoxicity.